Apollo – Greek god - Petrosyan, Armen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The names of Troy and Ilion (Τροία, Ἴλιον/Ἴλιος) go back to the toponyms Taruisa and Wilusa of the Hittite sources. The Trojan prince Paris, whose second name is Ἀλέξανδρος (Alexandros) has a historical prototype in the person of King Alaksandu of Wilusa, who sealed a treaty with the Hittite king Muwatalli II circa 1280 BC and thus lived for several decades before the date ascribed to the legendary Trojan War. In the treaty of Alaksandu and Muwatalli the gods of Troy-Wilusa are evoked: the first is the thunder/storm god of army, the name of the second is erased and the third one is Appaliuna (KUB 21.1 iv 27-28). Alaksandu and Apaliuna have no analogues in the onomastics of ancient Anatolia. Obviously, they are the cuneiform renderings of the Greek Alexandros and Apollo (Ἀπόλλων < *Apelyōn).